SIGNIFIKANSI GURU AGAMA KATOLIK PROFESIONAL - Fatlolon, Costantinus (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2015)
The professional catholic teacher of Religion is most significant for the faithful and the local community. The central theme of this article is, that a catholic teacher of Religion does not just function (1) as a professional instructor of the subject of Religion, but (2) most of all as a professional catechist who proclaims the Gospel and the doctrine of the Church and teaches the faithful and the local community by means of providing excellent thoughts, word and moral deeds. Thus, to become a catholic teacher of Religion is a vocation which comes from God himself. This vocation has to be accompanied by professional competence: spiritual, moral, social, individuality and intellectual.